PENGARUH OWNERSHIP PERUSAHAAN TERHADAP EARNING MANAGEMENT MELALUI EXECUTIVE COMPENSATION SEBAGAI VARIABEL INTERVENING PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nosa Andhika; Devie Deviesa (Business Accounting Review, 2017)
This research was conducted to find out the influence of Ownership Against Executive Compensation Through Earning Management as intervening variable in manufacturing industry listed in Indonesia Stock Exchange. Ownerships became one of the most important variables that can measure ability. The other variables such as Executive Compensation contributing in creating Earning Management of the company.Data that analysis techniques used in this research was the partial least square to describe the relationships among variables. The research results showed that the ownership and Earning Management affect the Executive Compensation in a positively and significantly at the Manufacture industry listed in Indoesia Stock Exchange.